2007
DOI: 10.1111/j.1524-4725.2007.33208.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Horn Malignant Melanoma

Abstract: have indicated no significant interest with commercial supporters.C utaneous horns are relatively uncommon lesions in clinical practice. They arise as a variably sized protrusion of keratotic, cohesive material organized in the shape of a conical horn, often located on the face or in sun-exposed areas. Their variable origin from benign or malignant/premalignant conditions is a known fact as well as the need in performing a histopathologic study of each excised lesion to determine the exact nature of the disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…It has been said that large or giant cutaneous horns are commonly derived from a malignant base. 3 Excisional biopsy with histologic examination of the base is necessary to determine the best therapy, which would be dictated by the diagnosis of the underlying lesion and by the apparent adequacy of removal. 5 Our patient might have had LM lesion for approximately 20 years, but it had become larger in the previous 5 to 6 months and had a protrusion during the last month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been said that large or giant cutaneous horns are commonly derived from a malignant base. 3 Excisional biopsy with histologic examination of the base is necessary to determine the best therapy, which would be dictated by the diagnosis of the underlying lesion and by the apparent adequacy of removal. 5 Our patient might have had LM lesion for approximately 20 years, but it had become larger in the previous 5 to 6 months and had a protrusion during the last month.…”
Section: Discussionmentioning
confidence: 99%
“…They arise as a variably sized protrusion of keratotic, cohesive material organized in the shape of a conical horn, often located on the face or in sunexposed areas. 3,4 These lesions are most often benign, with hyperkeratosis being superimposed on an underlying seborrheic keratosis, verruca vulgaris, angiokeratoma, molluscum contagiosum, or trichilemmoma approximately 60% of the time. 5,6 It has been found that giant cutaneous horns are commonly derived from a malignant lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is indicated not only because it is an immediate treatment but also because it considers the possibility of the existance of a premalignant or malignanton lesion on the basis with developmental tendencies. The surgical excision should be as conservative as possible and should also garantee a sufficient security margin 8,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of choice is the surgical excision of the lesion to the healthy tissue [17,20,21], followed by a histopathological examination in order to confi rm the diagnosis [6,13,18,22,23], the real point of interest being not the cutaneous horn, but the underlying lesion [1].…”
Section: Introductionmentioning
confidence: 99%